Availability and Adequacy of Curriculum Resources for Mechanical Trade Instruction: A Study on Technical Colleges in Anambra State, Nigeria - Cheta; Akudolu; James (Journal of Research in Industrial Technology and Educational Studies, 2026)
The research is aimed at examining the availability and adequacy of curriculum resources for the instructional delivery of mechanical trade students in technical colleges in Anambra State, Nigeria. Specifically, the study provides empirical evidence on the current state of human and material/physical resources available and their adequacy for teaching mechanical trade students in both federal and state technical colleges in Anambra State, Nigeria. A descriptive survey research design was adopted for the study. The study was guided by one research question, and one corresponding null hypothesis was tested. The target population comprised four technical staff, consisting of two-unit head technical teachers and two technicians, drawn from one federal and one state technical college that have been officially accredited by the National Board for Technical Education (NBTE) to offer Mechanical trade programme in Anambra State, Nigeria. A census approach was adopted; hence, no sampling procedure was used. The instrument for data collection was a 228- item observational checklist titled “Availability and Adequacy of Curriculum Resources for Mechanical Trade Instruction Questionnaire (AACRMTIQ)”. The instrument was developed using the NBTE minimum standard benchmark, which outlines the required human and material resources for effective instructional delivery of technical education in Nigeria. Since the NBTE benchmark was a standardized and officially approved instruction for accreditation, no further validity and reliability tests were conducted. Percentage was used to answer research question, while chi-square was used to test the null hypothesis at the 0.05 level of significance. The findings revealed that the curriculum resources for the instructional delivery of Mechanical trade students in both federal and state technical colleges were inadequately available, hence were below NBTE standards. The study concluded that adequate provision of curriculum resources will enable technical colleges to achieve the philosophy underlying their establishment. Based on the finding, it was recommended that Federal and State government should establish sustainable funding mechanism such as special intervention funds or public-private partnership (PPPs) to ensure consistent upgrade and maintenance of resources in technical colleges.